The Effect Of Performance-Based Training (PBK) and Work Environment on Employee Competency Through Emotional Intelligencefor Distribution Employees Of PT PLN (Persero) UID North Sumatera - Abdullah Sani Samosir; Sri Rahayu (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study seeks to analyze the influence of Performance-Based Training (PBT) and the Work Environment on Employee Competence, with Emotional Intelligence serving as a mediating variable among distribution employees at PT PLN (Persero) UID North Sumatra. A quantitative research design was applied, with data collected through questionnaires distributed to 40 respondents. The data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) to examine both direct and indirect relationships among the research variables. The findings reveal that Performance-Based Training and the Work Environment have a positive and significant effect on Emotional Intelligence as well as Employee Competence. Moreover, Emotional Intelligence is proven to mediate the relationship between Performance-Based Training and the Work Environment on Employee Competence. These results emphasize the importance of effective performance-based training programs and the creation of a supportive work environment in enhancing employee competence through the development of emotional intelligence.